Keratosis follicularis spinulosa decalvans in a 15 months Cypriot girl - Asli Kaptanoglu; Ceyhun Dalkan; Fusun Baba (Wolters Kluwer Medknow Publications, 2016)
Keratosis follicularis spinulosa decalvans (KFSD) is a rare disease with unknown etiology. It clinically presents with diffuse follicular hyperkeratosis of scalp which progress to atrophy, cicatricial alopecia, and photophobia. The lesions start in chilhood and an aggrevasion occurs after puberty by the development of scalp pustules with bacterial infection and causes both functional and cosmetic discomfort. Here, we report a Cypriot girl that diagnosed KFSD that do not have any family history.